RAINFALL–RUNOFF SIMULATION FOR SUSTAINABLE IRRIGATION WATER MANAGEMENT IN TROPICAL AGRICULTURAL CATCHMENT - Abd Rakhim Nanda (Yayasan Nusantara Hasana Berdikari, 2026)
Rainfall–runoff processes play a crucial role in determining irrigation water availability in tropical agricultural catchments. This study develops a rainfall–runoff simulation framework for sustainable irrigation water management by integrating rainfall characterization, SCS-CN runoff estimation, runoff coefficient analysis, effective runoff availability, irrigation water demand, water balance, Surplus–Deficit Ratio, and Irrigation Sustainability Index. Monthly rainfall data were used to estimate runoff depth and runoff-derived water availability, while irrigation demand was evaluated based on crop water requirement and effective water availability. The results show that runoff generation is highly seasonal, with high runoff coefficients during wet months and low runoff response during dry months. The ISI results indicate highly sustainable irrigation conditions in January, February, and December, sustainable conditions in March and November, and critical conditions from June to September. The proposed framework supports runoff harvesting, storage optimization, rotational irrigation, crop calendar adjustment, and priority-based water allocation.